European Security and Transatlantic Relations after 9/11 and the Iraq War
XIII, 271 p.
Keywords: At a time of unprecedented turmoil in the transatlantic relationship, as America asserts its right to act unilaterally to defend itself against terrorism and Europeans are increasingly aggressive in promoting a multilateralist approach to security issues, this book examines the post-9/11 and Iraqi war security environment, especially the impact on NATO and transatlantic relations as the European Union seeks to build a unified foreign and defence policy that will enable Europeans to play a fuller role in the international system.